SOCIAL DEVELOPMENT IMPROVEMENT OF CHILDREN AGED 5-6 YEARS THROUGH TRADITIONAL MAKASSAR GAME SONGKOK-SONGKOK JANGANG - Andi Rezeky Amaliah; Eka Damayanti; Ahmad Afiif (International Conference on Social and Islamic Studies, 2021)
This study aims to prove the increase in the social development of children aged 5-6 years through traditional Makassar songkok-songkok jangang games in Nurul Falah Kindergarten, Bontomarannu Village, Kec. Bontotiro, Bulukumba Regency. This study used a quantitative approach to the type of quasi-experimental research, with a research design of one group pretest-posttest design. The number of samples used were 12 children aged 5-6 years. The instrument used in the study was an observation sheet, and it was analyzed using non-parametric statistics using the Wilcoxon-signed ranking test. The results showed that there was a difference in the average value of children's social development before and after playing the traditional Makassar songkok-songkok jangang game as evidenced by the p-value of 0.002 (p 0.05). This is proved by the increase in the average score before (average 28.75) to the average value of children's social development after (average 50.17) playing the traditional Makassar songkok-songkokjangang in Nurul Falah Kindergarten, Bontomarannu Village. district. Bontotiro, Bulukumba Regency. An increase in the social development of children aged 5-6 years through traditional Makassar games, songkok-songkok, does not imply that teachers or parents of children continue to traditionalize traditional games in children and develop them based on their era.